2006
DOI: 10.1242/jcs.03077
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Tie2 by angiopoietin-1 and angiopoietin-2 results in their release and receptor internalization

Abstract: The receptor tyrosine kinase Tie2 is highly expressed in endothelial cells and is crucial for angiogenesis and vascular maintenance. The ligands for Tie2 are the angiopoietins, of which angiopoietin-1 and angiopoietin-2 have been the most studied. Angiopoietin-1 has been characterized as the primary activating ligand for Tie2 whereas the role of angiopoietin-2 remains controversial; activating Tie2 in some studies and inhibiting Tie2 in others. Our studies were aimed at understanding the regulation of Tie2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
116
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 45 publications
15
116
2
Order By: Relevance
“…Moreover, membraneassociated centripetal trafficking also regulates the Ang1/Tie2 signaling pathway. Approximately 70% of phosphorylated Tie2 is internalized from the plasma membrane and targeted for degradation in lysosomes within 30 min of Ang1 stimulation in endothelial cells (6). The proper elucidation of the role of these signaling pathways in PAH requires our appreciation of the issue of regulated membrane-associated centripetal trafficking from the plasma membrane to the cell interior (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, membraneassociated centripetal trafficking also regulates the Ang1/Tie2 signaling pathway. Approximately 70% of phosphorylated Tie2 is internalized from the plasma membrane and targeted for degradation in lysosomes within 30 min of Ang1 stimulation in endothelial cells (6). The proper elucidation of the role of these signaling pathways in PAH requires our appreciation of the issue of regulated membrane-associated centripetal trafficking from the plasma membrane to the cell interior (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For each image, the "background" was adjusted to 0 pixels to reduce variance in intensities between experimental and control sets. Colocalization analyses were performed using the NIH ImageJ Just Another Colocalization Plugin (JACoP) (6). JACoP directly provides the Pearson R correlation, Manders' M1 and M2 coefficients, and Costes' randomization coefficients for a pair of images in the red and green channels.…”
Section: Methodsmentioning
confidence: 99%
“…ANG-2 was first identified as a natural antagonist of ANG-1/Tie-2 signalling in ECs 11 . However, subsequent studies report conflicting results demonstrating its pro-angiogenic activity in vitro or in vivo 12,13 . ANG-2 also sensitizes ECs to respond to inflammatory cytokines, such as tumour-necrosis factor-a, and thus enhances angiogenesis triggered by inflammation 14 .…”
mentioning
confidence: 99%
“…On the contrary, Ang1 stimulation decreased BiFC intensity after 30 min. This suggests that internalization and degradation of Tie2 was induced after Tie2 phosphorylation (30). Interestingly, we found that Tie2YIA/LAS prominently enhanced BiFC intensity under Ang1 stimulation for 1 h (Fig.…”
Section: Tie2yia/las Monomer Mutants Can Be Dimerized and Phosphorylamentioning
confidence: 63%
“…can form ligand-independent inactive dimers; it has therefore been suggested that receptor dimerization and activation are mechanistically distinct and separable events (19,30). Next, we analyzed whether Ang1 binding to the inactive monomer mutant Tie2YIA/LAS induced dimerization and activation of Tie2.…”
Section: Tie2yia/las Monomer Mutants Can Be Dimerized and Phosphorylamentioning
confidence: 99%